Comparative study of the chemical composition, antibacterial activity and synergic effects of the essential oils of Croton tetradenius baill. And C. pulegiodorus baill. Against Staphylococcus aureus isolates. (July 2021) - Rocha, Renan Rhonalty; Matos, Maria Nágila Carneiro; Guerrero, Jesús Alberto Pérez; Cavalcante, Rafaela Mesquita Bastos; Melo, Ramaiana Soares; Azevedo, Águida Maria Albuquerque; Pereira, Antônio Mateus Gomes; Lopes, Pedro Henrique Ribeiro; Rodrigues, Tigressa Helena Soares; Bandeira, Paulo Nogueira; Gomes, Geovany Amorim; Catunda Junior, Francisco Eduardo Aragão; et al.
Abstract: The aim of this work was to evaluate the chemical composition and antibacterial activity of Croton tetradenius Baill. (CTEO) and C. pulegiodorus Baill. (CPEO) essential oils against Staphylococcus aureus, and their synergism with antibiotics. The essential oils (EOs) were extracted by hydrodistillation and chemically characterized by gas chromatography-mass spectrometry (CG-MS) and gas chromatography with flame ionization detection (CG-FID). The antimicrobial action of the EOs was tested against two standard strains and four clinical isolates of S. aureus using the disk-diffusion agar method and the microdilution assay. The bacterial kinetic growth was also determined. The synergistic effect between EOs and antimicrobials was analyzed by the checkerboard test. CTEO and CPEO yielded 0.47 and 0.37% w/w and the most common components were p -cymene (28.24%), camphor (17.76%) and α-phellandrene (8.98%), and trans -chrysanthenyl acetate (27.05%), α-terpinene (19.21%) and p -cymene (12.27%), respectively. The disk-diffusion test showed that the bacteria are sensitive to the agents tested. The MIC in the presence of the CTEO it was 4000 μg/mL, while for the CPEO it was 8000 μg/mL, except for clinical isolate 4B. The MBC for strains treated with CTEO were 8000 μg/mL, with the exception of isolates 8B and 0 A 4000 μg/mL. For the CPEO, all strains showed a concentration above 8000 μg/mL. The growth curve showed that CTEO and CPEO altered growth kinetics, delaying the lag phase and reducing the log phase. In combination with antibiotics, both essential oils showed synergisms effect with oxacillin and ampicillin, and additive effect with benzylpenicillin. CTEO and CPEO showed antibacterial action against S. aureus strains, showing as a promise natural alternative in clinical therapy. Highlights: The major component was p -cymene in CTEO and trans -chrysanthenyl acetate in CPEO. A new chemotype rich in trans -chrysanthenyl acetate was found in CPEO. Both essential oils tested showed antibacterial action against S. aureus strains. CTEO and CPEO delayed and reduced the log phase during growth curve. CTEO and CPEO when associated with antibiotics displayed high synergistic action.